DEKONSTRUKSI PENGETAHUAN DALAM MAKNA SIMBOLIK SENI UKIRAN TORAJA: SEBUAH TINJAUAN EPISTEMOLOGIS - Aswat, Fajar (Nuansa Journal of Arts and Design, 2025)
This research adopts a literature review method with a deconstructive approach to analyze various written sources, such as journal articles, books, and academic documents. The findings reveal that traditional motifs, such as pa’tedong (buffalo), pa’bare allo (sun), and pa’manuk londong (rooster), which once held sacred functions, have shifted to serve as decorative elements and modern commodities. The deconstruction process unveils ambiguities in symbolic meanings, enabling new interpretations relevant to modern contexts.Theoretically, this study highlights that Toraja carving art is not merely a cultural artifact but also an epistemological medium reflecting the social and spiritual dynamics of its community. This transformation in meaning poses challenges to cultural preservation while also opening opportunities for innovation. This research contributes to bridging tradition and modernity, ensuring the sustainability of Toraja carving art amidst the challenges of globalization.